2019
DOI: 10.1016/j.geomphys.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Tensor hierarchies and Leibniz algebras

Abstract: Tensor hierarchies are algebraic objects that emerge in gauging procedures in supergravity models, and that present a very deep and intricate relationship with Leibniz (or Loday) algebras. In this paper, we show that one can canonically associate a tensor hierarchy to any Loday algebra. By formalizing the construction that is performed in supergravity, we build this tensor hierarchy explicitly. We show that this tensor hierarchy can be canonically equipped with a differential graded Lie algebra structure that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…It has recently been shown that any Leibniz algebra canonically (via a differential graded Lie algebra, or equivalently, an infinity-enhanced Leibniz algebra [58]) gives rise to an L ∞ algebra [59]. It would be interesting to compare the L ∞ algebra constructed in that way with the one presented here, not least since in the application to gauged supergravity, the relevant differential graded Lie algebra can be understood as coming from a tensor hierarchy algebra [60,61].…”
Section: Discussionmentioning
confidence: 96%
“…It has recently been shown that any Leibniz algebra canonically (via a differential graded Lie algebra, or equivalently, an infinity-enhanced Leibniz algebra [58]) gives rise to an L ∞ algebra [59]. It would be interesting to compare the L ∞ algebra constructed in that way with the one presented here, not least since in the application to gauged supergravity, the relevant differential graded Lie algebra can be understood as coming from a tensor hierarchy algebra [60,61].…”
Section: Discussionmentioning
confidence: 96%
“…We can now derive some further consequences from the Leibniz relations, in particular from the closure relation (1.7), 4) and symmetrizing (2.3) in x, y we have…”
Section: Leibniz Algebrasmentioning
confidence: 99%
“…In this paper we construct the general gauge theory of Leibniz-Loday algebras [1][2][3][4][5][6], which are algebraic structures generalizing the notion of Lie algebras. These structures have appeared in the context of duality covariant formulations of gauged supergravity [7][8][9][10] and of string/M-theory [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The recent resurgence of physics interest in L ∞ -algebras (e.g. [27][28][29][30][31][32][33][34][35][36][37][38]) mostly centres on gauge symmetries of classical theories. (Most relevant here is [28], which articulates the lore that classical BV master actions have canonical associated L ∞ -algebras [16,[39][40][41][42][43][44][45][46][47][48][49][50]).…”
Section: Jhep07(2019)115mentioning
confidence: 99%